Crystal structure of nanocrystalline Pr5Co19 compound and its hydrogen storage properties. (3rd April 2020) - Bouzidi, W.; Patout, L.; Charai, A.; Mliki, N.; Bessais, L.
Abstract: The present study focuses on the structure and pressure-composition (P–C) isotherm measurements of nanocrystalline Pr5 Co19 hydrides. The crystal structure and hydrogenation properties of Pr5 Co19 are investigated by X-ray diffraction, refined using Rietveld method, and by transmission electron microscopy (TEM). This intermetallic compound crystallizes in the rhombohedral (3R) with Ce5 Co19 -type structure. The pressure-composition isotherm of Pr5 Co19 was measured at room temperature. A single plateau was observed during the absorption-desorption process, the reversible hydrogen capacity reached 10 H/f.u (0.4 H/M). A peak broadening was observed in the X-ray diffraction (XRD) profile after hydrogenation, with no detection of any amorphous phase. The crystal structure of the Pr5 Co19 H x hydrides has not been changed, it always conserves the rhombohedral structure (space group R 3 ¯ m ). The lattice parameters have increased with hydrogen content leading to an anisotropic expansion of the unit cell volume.